2017
DOI: 10.13057/biodiv/d180426
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Occurrence and cluster analysis of palm oil (Elaeis guineensis) fruit type using two-dimensional thin layer chromatography

Abstract: Arifiyanto D, Basyuni M, Sumardi, Putri LAP, Siregar ES, Risnasari I, Syahputra I. 2017. Short Communication: Occurrence and cluster analysis of palm oil (Elaeis guineensis) fruit type using two-dimensional thin layer chromatography. Biodiversitas 18: 1487- 1492. The problems that have been faced by palm oil breeders are the length of time and high costs to discover the type of palm oil (Elaeis guineensis) fruit namely Dura, Pisifera, or Tenera, before using as a seed parent. These conditions are ineffective a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 16 publications
(44 reference statements)
2
9
0
2
Order By: Relevance
“…The results of isoprenoid analysis in oil palm leaf tissue (Table 1) showed that leaf tissue of oil palm has only type II lipid pattern. These findings supported the previous study by Arifiyanto et al (2017) that type II lipid was present in oil palm Dura, Pisifera, and Tenera, oil palm infected with Ganoderma boninense (Afandy et al 2019), oil palm in different land use (Basyuni et al 2018).…”
Section: Polyisoprenoids Analysis By Two-dimensional Thin-layer Chromatographysupporting
confidence: 91%
See 1 more Smart Citation
“…The results of isoprenoid analysis in oil palm leaf tissue (Table 1) showed that leaf tissue of oil palm has only type II lipid pattern. These findings supported the previous study by Arifiyanto et al (2017) that type II lipid was present in oil palm Dura, Pisifera, and Tenera, oil palm infected with Ganoderma boninense (Afandy et al 2019), oil palm in different land use (Basyuni et al 2018).…”
Section: Polyisoprenoids Analysis By Two-dimensional Thin-layer Chromatographysupporting
confidence: 91%
“…The results showed that leaf tissue and mesocarp had various carbon chain lengths. The length of the polyisoprenoid carbon chains in oil palms varies according to tissue type although in the same species and forms a particular dominant polyisoprenoid family (Arifiyanto et al 2017). The difference in the length of the polyisoprenoid carbon chain in oil palm leaves (E. guineensis) is caused by several factors, including the age of tissue (tissue aging), salinity stress, tissue differences (Basyuni et al 2018).…”
Section: Quantification Of Polyisoprenoid Compoundsmentioning
confidence: 99%
“…Beberapa bakteri alami Indonesia berhasil diisolasi dari daerah tercemar dan memiliki kemampuan akumulasi tembaga. Bakteri ini dapat bertindak sebagai biosorben sehingga dapat menyisihkan tembaga dari lingkungan (5) . Populasi bakteri di daerah yang tercemar logam berat akan mengembangkan suatu proses adaptasi untuk menjadi resisten terhadap logam berat.…”
Section: Latar Belakangunclassified
“…Koloni bakteri diinokulasikan ke dalam medium LB padat yang diberi CuSO4 konsentrasi terntentu kemudian diinkubasikan pada suhu 37 o C selama dua hari. Koloni yang tumbuh diuji lagi pada konsentrasi CuSO4 yang lebih tinggi hingga isolat bakteri tidak mampu tumbuh (5) . Bakteri yang paling resisten dipilih dan digunakan untuk isolasi plasmid dan analisis gen 16s rDNA.…”
Section: Uji Resistensiunclassified
“…Dolichol is present in nearly all plant tissues, particularly in the roots (Basyuni et al 2016(Basyuni et al , 2017a(Basyuni et al , b, 2018a, from the shorter (C25-C40), medium-chain (C65-C85), and longer chain length (C90-C140). In Arifiyanto et al (2017) research, the length of the polyisoprenoid carbon chain in oil palms varies according to each tissue or organ even though it is in the same species but comes from different growth phases and the type of fruit produced.…”
Section: Introductionmentioning
confidence: 99%